Effects of Land Use on the Soil Microbial Community in the Songnen Grassland of Northeast China - Liu, Guofu; Bai, Zhenjian; Cui, Guowen; He, Wenhua; Kongling, Zelai; Ji, Guoxu; Gong, Hao; Li, Dandan (Frontiers in Microbiology, 2022)
Land use change significantly changes the plant community composition and soil properties of grasslands and thus affects multiple functions and services of grassland ecosystems. However, the response mechanisms of soil microorganisms, key drivers of the nutrient cycle and other soil functions, during changes in grassland use type and associated vegetation are not well understood. In this study, Illumina high-throughput sequencing was used to analyze the changes in the soil microbial community structure of four grassland use types (exclosure (EL), mowed land (ML), grazed land (GL) and farmland (FL)) in the Songnen Plain of Northeast China. The results showed that the FL and EL had significantly higher soil total nitrogen (TN), and lower soil electrical conductivity (EC) and pH than GL and ML. In contrast, the GL and ML had higher soil bulk density (BD) and organic matter, respectively, than the other land use types. In addition, the values of the Shannon diversity and Pielou's evenness indexes were highest in the EL of all the land use types. Based on the high-throughput sequencing results, we observed high levels of α diversity in the FL for both bacteria and fungi. A structural equation model (SEM) revealed that pH and EC had a direct and positive effect on the bacterial community structure and composition. In addition, plant taxonomic diversity (according to the Shannon diversity and Pielou's evenness indexes) indirectly affected the bacterial community composition via soil pH and EC. Notably, fungal composition was directly and positively correlated with soil nutrients, and the value of Pielou's evenness index changed with land use type. In conclusion, soil properties and/or plant diversity might drive the changes in the soil microbial community structure and composition in different grassland use types.